A pilot study on neurological manifestations and antibodies against antigens in children with hematological and other cancers. - Polizzi, A; Ruggieri, M; Clover, L; La Spina, M; Pulvirenti, A; Amyes, E; Vincent, A (2013)
BACKGROUND: Paraneoplastic neurological syndromes (PNS) are most commonly recognized in adults with cancer and can often be identified by the presence of serum antibodies to neuronal proteins that are also expressed by the associated tumor. In children: (a) little emphasis is given to the possibility of paraneoplastic neurological involvement; and (b) few studies investigated the presence of anti-neuronal antibodies. OBJECTIVE: To run a pilot study on the spectrum of PNS and presence of antibodies to neural antigens in children with malignancies. METHODS: 23 children (7 boys; 16 girls, aged 4 months to 16 years) with hematological or other cancers were examined for neurological manifestations and for antibodies to the neuronal antigens that are frequently detected in adult patients with PNS. RESULTS: Ten of the 23 children had neurological symptoms (and/or positive antibodies): in 6/10 neurological manifestations could be explained by tumor invasion or chemotoxicity or were probably incidental; a child with neuroblastoma developed opsoclonus-myoclonus syndrome without detectable anti-neuronal antibodies; antibodies to a Tr-like cerebellar antigen [associated to no neurological signs and later enuresis], to voltage-gated potassium channels [associated to sensory signs] and to glutamic acid decarboxylase [associated to multifocal myoclonus] were found in one child each. Results were compared with age- and sex-matched control groups. CONCLUSION: These results suggest that PNS, though surprisingly not so uncommon in children, may be associated with immune responses to distinct neuronal antigens. Further work is needed to determine whether screening for new antibodies to neuronal antigens could be a useful aid in the diagnosis and prognosis of neurological syndromes in children.